2005
DOI: 10.1103/physrevb.71.024533
|View full text |Cite
|
Sign up to set email alerts
|

Carbon substitution inMgB2single crystals: Structural and superconducting properties

Abstract: The growth of carbon-substituted magnesium diboride Mg͑B 1−x C x ͒ 2 single crystals with 0 ഛ x ഛ 0.15 is reported, and the structural, transport, and magnetization data are presented. The superconducting transition temperature decreases monotonically with increasing carbon content in the full investigated range of substitution. By adjusting the nominal composition, T c of substituted crystals can be tuned in a wide temperature range between 10 and 39 K. Simultaneous introduction of disorder by carbon substitu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
245
0
2

Year Published

2005
2005
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 244 publications
(268 citation statements)
references
References 41 publications
21
245
0
2
Order By: Relevance
“…The change in the lattice parameters can be converted into an actual amount of carbon substitution by comparing with the results on single crystals. 9 As shown in Fig. 2͑c͒, more carbon incorporation is achieved at a lower heat-treatment temperature for carbohydrate doping.…”
Section: Resultsmentioning
confidence: 83%
“…The change in the lattice parameters can be converted into an actual amount of carbon substitution by comparing with the results on single crystals. 9 As shown in Fig. 2͑c͒, more carbon incorporation is achieved at a lower heat-treatment temperature for carbohydrate doping.…”
Section: Resultsmentioning
confidence: 83%
“…5,11 In both cases ͑SiC and CNT͒ part of carbon dissolves into the MgB 2 structure during the fabrication process, 13,19 and the shift in the a-lattice parameter, obtained from x-ray diffraction, can be used as a measure of the actual amount of C ͑x͒ in the Mg͑B 1−x C x ͒ 2 structure. 22 The synthesis temperature, lattice parameters, and x values obtained from fitting the single crystal data of Kazakov et al 25 and the neutron diffraction data of Avdeev et al 27 are listed in Table I. Figure 1 shows the normalized dc magnetization as a function of temperature ͑T͒, measured with a Quantum Design® superconducting quantum interference design magnetometer, in a field of 20 Oe using a zero field cooling process.…”
Section: Methodsmentioning
confidence: 99%
“…Although the effect of carbon substitution is one of the most studied in MgB 2 , the results on C solubility and the effect of C doping on T c , J c , and H c2 reported so far vary significantly, due to precursor materials, fabrication techniques, and processing conditions used. [20][21][22][23][24][25] Recently, Matsumoto et al 26 reported that J c in SiC-alloyed MgB 2 tapes depends on a complex relation between grain connectivity, H c2 , and flux pinning induced by grain boundaries and precipitates. However, the distinct effect of C incorporation through different routes in J c and H c2 is still not entirely understood.…”
Section: Introductionmentioning
confidence: 99%
“…It is well documented that B c2 can be enhanced significantly by various techniques [1,2,3,4,5,6,7,8,9,10,11]. Although the mechanisms involved in these changes are not yet fully understood, impurity scattering in both bands seems to play a major role.…”
Section: Consequences/strategymentioning
confidence: 99%
“…In MgB 2 thermal effects should play only a minor role due to its comparatively low Ginzburg number. Nevertheless, the critical currents become too small for power applications at fields well below H c2 , even at 4.2 K. Fortunately, the upper critical field of MgB 2 can be rather easily enhanced by certain preparation conditions [1,2,3], doping [4,5,6,7,8] or irradiation [9,10,11], and exceeds 30 T (at 0 K). Even for such "high-H c2 " materials, the application range is limited to around 10 T in polycrystalline samples.…”
Section: Introductionmentioning
confidence: 99%